(untitled) (Global Journal of Human-Social Science, 2024)
Introduction-This article explores some of the religious influences behind the development of capitalism in the modern world. It questions any conception of life that limits its objects or ideas to a singular causal series of actions. It forwards a view of life as a confluence of many forces in a constant state of interaction that come together in creating the world. It rejects any notion that might think capitalism or any system of nature and thought develops in an orderly sequence from a simple linear direction of cause and effect outside a multitude of influences that constitute a network of relations sharing reciprocal information. 1 What the article hopes to display is a few of the religious influences that served in the mix of a multitude of forces in developing the economic system called capitalism. It repudiates those who live in the binary and think it is possible to separate religion from society and the government.